Analysis of the Adherence to the Time of Doctor Visits in the Inpatient Installation - Fitrianti Adnan; Yuniar Lestari; Rosfita Rasyid (Newinera Publisher, 2025)
One of the national indicators of hospital quality is compliance with doctor's visit time, the achievement of the National Quality Index (INM) at the inpatient installation of Tk. III dr. Reksodiwiryo Padang Hospital in 2023 is 67%. This value is below the quality indicator standards that have been regulated by the Minister of Health Regulation No. 30 of 2022. This study is aimed at analyzing the adherence to doctor's visit time at the inpatient installation of Tk. III Dr. Reksodiwiryo Padang Hospital. The research used the mixed method method, the first stage was quantitative research with stratified random sampling techniques, then qualitative research was carried out with in-depth interviews with 14 informants, field observation and document review. Compliance with the doctor's visit time at the inpatient installation of Tk. III dr. Reksodiwiryo Padang Hospital based on research was obtained at 40%. The causes of non-compliance with doctor's visit time are the lack of the number of organic/permanent specialist doctors and the absence of an alarm to remind the doctor's visit time, the absence of clear regulations related to decrees, SOPs, and doctor's visit policies, the absence of a clear doctor's visit schedule, in addition to the DPJP's lack of understanding of the Regulation of the Minister of Health on visit time and the lack of optimal follow-up from monitoring and evaluating the compliance of doctor's visit time in inpatient installations.